Molecular evolution of GPCRs: 26Rfa/GPR103 - Ukena, Kazuyoshi; Osugi, Tomohiro; Leprince, Jérôme; Vaudry, Hubert; Tsutsui, Kazuyoshi (Journal of molecular endocrinology, 2014)
Neuropeptides possessing the Arg-Phe-NH2 (RFamide) motif at their C-termini (designated as RFamide peptides) have been characterized in a variety of animals. Among these, neuropeptide 26RFa (also termed QRFP) is the latest member of the RFamide peptide family to be discovered in the hypothalamus of vertebrates. The neuropeptide 26RFa/QRFP is a 26-amino acid residue peptide that was originally identified in the frog brain. It has been shown to exert orexigenic activity in mammals and to be a ligand for the previously identified orphan G protein-coupled receptor, GPR103 (QRFPR). The cDNAs encoding 26RFa/QRFP and QRFPR have now been characterized in representative species of mammals, birds, and fish. Functional studies have shown that, in mammals, the 26RFa/QRFP-QRFPR system may regulate various functions, including food intake, energy homeostasis, bone formation, pituitary hormone secretion, steroidogenesis, nociceptive transmission, and blood pressure. Several biological actions have also been reported in birds and fish. This review summarizes the current state of identification, localization, and understanding of the functions of 26RFaQRFP and its cognate receptor, QRFPR, in vertebrates.